1997
DOI: 10.1111/j.1746-1561.1997.tb03422.x
|View full text |Cite
|
Sign up to set email alerts
|

Coping With A New Society: The Unique Psychosocial Problems of Immigrant Youth

Abstract: When immigrant children and adolescents leave their country of origin to live in the United States, they leave behind a familiar language, culture, community, and social system. They also experience a variety of emotional and cognitive adjustments to the realities of life in the United States. Many of these conflicts and adjustments place immigrant children at increased risk for psychosocial problems, school failure, drug use, and other risk-taking behavior. Early identification of immigrant children at risk f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
68
0
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(75 citation statements)
references
References 9 publications
4
68
0
3
Order By: Relevance
“…In this study, criterion-related validity was examined by using the scale to predict students' depression and life satisfaction. Previous studies have demonstrated that people with higher levels of acculturative stress would have a higher probability of depression symptoms (Lin & Yi, 1997;James, 1997;SuarezMorales et al, 2007). Chinese students' depression was measured by Zung's Self-Rating Depression Scale (SDS, 1965).…”
Section: Methodsmentioning
confidence: 98%
See 3 more Smart Citations
“…In this study, criterion-related validity was examined by using the scale to predict students' depression and life satisfaction. Previous studies have demonstrated that people with higher levels of acculturative stress would have a higher probability of depression symptoms (Lin & Yi, 1997;James, 1997;SuarezMorales et al, 2007). Chinese students' depression was measured by Zung's Self-Rating Depression Scale (SDS, 1965).…”
Section: Methodsmentioning
confidence: 98%
“…Such a wide cultural distance creates a lot of conflicts regarding values, behaviors and norms for Chinese students, especially when they interact with local people (James, 1997). Unfamiliar with the cultures and values in the U.S., Chinese students may not be clear about the expectations of certain behaviors and their roles.…”
Section: Acculturative Stress and Cultural Distancementioning
confidence: 99%
See 2 more Smart Citations
“…Second, immigration itself is a stressful process, typically associated with grief, loss of family and friends, and cultural changes (Hicks et al, 1993;James, 1997), and these diverse demands may increase the vulnerability and emotional distress of migrant children (Pawliuk et al, 1996).…”
Section: The Wellbeing Of Migrant Adolescentsmentioning
confidence: 99%